2006
DOI: 10.1111/j.1399-3046.2006.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyomavirus (BK) in pediatric renal transplants: Evaluation of viremic patients with and without BK associated nephritis

Abstract: Polyoma BK virus (BKV) is emerging as a significant complication in renal transplantation, which may lead to renal dysfunction and graft loss caused by BK nephritis (BKN). We report the management and outcome of 20 children who developed BK viremia. Serum polymerase chain reaction (PCR) for BKV DNA was measured monthly for the first year in transplant recipients and every six months thereafter, or for unexplained creatinine elevation. With seroconversion to +PCR, patients were managed with reduction of immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 6 publications
5
49
0
1
Order By: Relevance
“…However, some studies show that the rate of decline of GFR can be slowed by 40% with a reduction in immunosuppression alone [22]. On average, the burden of graft loss varies and may range from 15% in adults to 50% in the pediatric population [23].…”
Section: Treatmentmentioning
confidence: 99%
“…However, some studies show that the rate of decline of GFR can be slowed by 40% with a reduction in immunosuppression alone [22]. On average, the burden of graft loss varies and may range from 15% in adults to 50% in the pediatric population [23].…”
Section: Treatmentmentioning
confidence: 99%
“…A comparison of cidofovir-treated with nontreated patients has been described but not in a randomized controlled trial (88,89 (85,91,92), but not in others (87,93). (94 or VP1 mRNA (14,42,43,51,52,64,99 (39,41,51), or plasma BKV loads of >4 log 10 geq/mL is more than 50% (51,52,103) (52,105,106 (26,30,36). Single-center studies report that enzyme immunoassays (EIA) using BK virus-like particles (BKVLP) assembled in vitro from recombinant VP1 may be more sensitive but equally specific compared to hemagglutination inhibition and neutralization tests (26,34,112 (26,34,75,(115)(116)(117)(118)(119).…”
Section: Diagnosis Of Pyvanmentioning
confidence: 99%
“…Rocha et al (49) reported no allograft loss and clearance of viruria in seven patients after discontinuation of MMF and reduction in calcineurin inhibitor dosage despite a mean creatinine of 3.2 mg/dl at diagnosis compared with persistent viruria and allograft loss in two recipients after only reduction in MMF and modification of calcineurin inhibitor. Dosage reduction of the adjuvant agent and calcineurin inhibitor in pediatric patients failed to clear viremia with 50% graft loss (89). Dosage reduction of the adjuvant agent and calcineurin inhibitor in adults failed to improve tubular BKV burden with a rising mean creatinine (51).…”
Section: Late Bkv Nephropathymentioning
confidence: 99%